2021
DOI: 10.1002/wfs2.1447
|View full text |Cite
|
Sign up to set email alerts
|

Research trends in forensic science: A scientometric approach to analyze the content of the INTERPOL reviews

Abstract: The use of forensic evidence has become indispensable in many countries and jurisdictions around the world; however, the dissemination of research advancements does not necessarily directly or easily reach the forensic science community. Reports from the INTERPOL International Forensic Science Managers Symposium outline major areas that are of interest to forensic practitioners across the INTERPOL member countries. The information contained in the INTERPOL reports is extensive but can be challenging to process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…In the IFSMS reports, 32.4% (n = 135 out of 417) of the listed references were indexed in Scopus and/or Web of Science, and only 28.8% (120 out of 417) of those matched outputs by the citation database following a specific search (reduced dataset based of fibres associated with textiles and garments). These results were found similar to observations made for other evidence types listed in the IFSMS reports [ 12 ] for which 3216 out of 14,718 (21.9%) references listed across 13 evidence types and indexed on Scopus were found also present in targeted searches relevant to the individual evidence types, for example toxicology, explosives, glass or paint. This disparity may seem surprising since the IFSMS reports have the purpose of communicating the latest scientific discoveries from the previous three years, with one reasonable source being from the recorded information contained in citation databases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the IFSMS reports, 32.4% (n = 135 out of 417) of the listed references were indexed in Scopus and/or Web of Science, and only 28.8% (120 out of 417) of those matched outputs by the citation database following a specific search (reduced dataset based of fibres associated with textiles and garments). These results were found similar to observations made for other evidence types listed in the IFSMS reports [ 12 ] for which 3216 out of 14,718 (21.9%) references listed across 13 evidence types and indexed on Scopus were found also present in targeted searches relevant to the individual evidence types, for example toxicology, explosives, glass or paint. This disparity may seem surprising since the IFSMS reports have the purpose of communicating the latest scientific discoveries from the previous three years, with one reasonable source being from the recorded information contained in citation databases.…”
Section: Discussionsupporting
confidence: 88%
“…To facilitate and share the latest advancements in forensic research, reports from the INTERPOL International Forensic Science Managers Symposium (IFSMS) outline and summarise major areas of interest to forensic science practitioners across the INTERPOL member countries [ 11 ]. The information contained in the INTERPOL IFSMS reports can be seen as complementary to, for example, citation databases, but their extensive contents remain presented as literature reviews and these are challenging to process information from, see for example [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only those that were identified as relevant and meaningful for readers were reported. Besides the specific reviews, we can recommend the following ones, for they addressed broad topics: summary of the research projects presented at the 2015 and 2017 IFRG meetings [ 199 ]; meta-analysis of the Interpol reports published between 2004 and 2019 [ 200 ]; evolution of the publication trends in friction ridge discipline between 2005-2009 and 2010–2014 [ 2 ].…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…Their study identified the field's leading countries, organizational affiliations, language, form, and funding agencies. The study's findings provide valuable insights into research trends in forensic science(12).Jozi and Nourmohammadi (2022) study utilized scientometric analysis to examine the scientific publications and patents in pathology and forensic medicine globally and the citation relationship between them from 2011 to 2020. The study found poor collaboration between academia and industry and highlighted North America as the busiest pathology and forensic medicine region.…”
mentioning
confidence: 99%
“…The study investigates the relationships between the 10 evidence types and provides a comprehensive overview of trends in forensic science research. A userfriendly R-Shiny application was also developed to explore the study outputs(12).…”
mentioning
confidence: 99%